SAE Technical Paper Series 2003
DOI: 10.4271/2003-01-2368
|View full text |Cite
|
Sign up to set email alerts
|

Development of Metal-impregnated Single Walled Carbon Nanotubes for Toxic Gas Contaminant Control in Advanced Life Support Systems

Abstract: The success of physico-chemical waste processing and resource recovery technologies for life support application depends partly on the ability of gas clean-up systems to efficiently remove trace contaminants generated during the process with minimal use of expendables. Highly purified metal-impregnated carbon nanotubes promise superior performance over conventional approaches to gas clean-up due to their ability to direct the selective uptake gaseous species based both on the nanotube's controlled pore size, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…-Carbon nanotubes are a relatively recently discovered material and therefore their impact on the environment and human health is not yet fully understood [35,43,44,61]. Although nanotubes do not exhibit acute toxicity, and therefore they are for example intentionally introduced into the human body to accelerate the mending of broken bones [33], or are used to filter the air in the life support systems of spacecraft [18]. It is uncertain, however, whether or not they have any negative longterm health effects resulting from interaction with the human body.…”
Section: Discussionmentioning
confidence: 99%
“…-Carbon nanotubes are a relatively recently discovered material and therefore their impact on the environment and human health is not yet fully understood [35,43,44,61]. Although nanotubes do not exhibit acute toxicity, and therefore they are for example intentionally introduced into the human body to accelerate the mending of broken bones [33], or are used to filter the air in the life support systems of spacecraft [18]. It is uncertain, however, whether or not they have any negative longterm health effects resulting from interaction with the human body.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that the carcinogenic effect is associated with the presence of precursors to the growth of nanotubes or other metal nanoparticles such as iron, nickel, cobalt, which can easily decorate the surface of nanotubes. On the contrary, nanotubes that were cleaned of any metal nanoparticles contamination were successfully used in the purification systems of manned spacecraft [14]. The successes of clinical trials are reported, where CNTs were deliberately introduced into the human body in place of the missing bone fragments in cases of multiple fractures; CNT serves in this case as a scaffold which initiates the process of bone healing [15].…”
Section: Introductionmentioning
confidence: 99%